An Evaluation of Assessment Designed by English Language Education Student Taechers During Teaching Parctice - Rintan Munirah; Refnaldi Refnaldi (Journal of English Language Teaching, 2020)
Assessment is the process which is done during teaching and learning process by the teachers in order to know sudents’ ability and monitor students’ development. An assessmnet supposed to have good content validity value. This research is aimed to evaluate the formal formative assessment designed by Englsih Language Education Student Teachers during teaching practice. The evaluation was done by considering the content validity of the assessment. The evaluation will be done on the formal formative assessment which is intended to assess speaking, reading, and writing skill. The instrumentation of this research is Content Validity Evaluation Rubrics. This is a descriptive research. In collecting the data, the researcher has collected the documents in the form of Daily Test. The findings of the research is the speaking, reading, and writing assessment designed by student teachers during teaching practice are categorized as valid seen from its content validity.